Synthesis of N-(2’-imidazolyl)-2- aminopyridyl Palladium Dichloride and its application as catalyst in Suzuki-Miyaura cross coupling reaction - Hashem, Md Abul; Sultana, Abeda (Journal of the Bangladesh Chemical Society, 2012)
The ligand N-(2′-imidazolyl)-2- aminopyridine 9 was prepared from imidazole. Compound 9 forms complex with Na2PdCl4 in methanol. The complex 10 (1.5 mmol %) was utilized in Suzuki-Miyaura cross-coupling reaction to prepare substituted biphenyls, terphenyls, and heterobiaryls in good to excellent yields. Keywords: N-(2′-imidazolyl)-2-aminopyridine ligand; Palladium Complexes; Palladacycles; Suzuki-Miyaura Cross Coupling; Biaryls; Terphenyls; Heterobiaryls; Suzuki-reaction. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9701 Journal of Bangladesh Chemical Society, Vol. 24(2), 123-134, 2011